The uncanny X-Men : an origin story - Thomas, Rich. (Marvel, 2011)
Tells the story of a boy named Charles Xavier who discovers that he is a mutant with special powers, how he decides to use those powers to protect humanity, and how he starts a school to teach mutants to use their super powers for good.